Exploring the corrosion resistance of the Ti20-Al20-V20-Fe20-Ni20 high-entropy alloy fabricated through spark plasma sintering - Uwa O. Uyor; Abimbola P.I. Popoola; Olawale M. Popoola (Journal of Alloys and Metallurgical Systems)
This study delves into investigating the corrosion behavior of HEAs (high entropy alloys) processed by the SPS (spark plasma sintering) production route The corrosion characteristics of the HEAs were explored by exposing them to acidic and salt media at both room temperature and 50 °C. Subsequently, The SEM (Scanning Electron Microscope) was employed in analyzing the impact of corrosion on the manufactured HEAs. OCP (open circuit potential) and PDP (potentiodynamic polarization) analyses were employed to gauge the susceptibility of the SPSed HEAs to corrosive environments. The OCP and PDP results demonstrated that the high entropy alloy produced at 1000°C had the lowest corrosion rates in both media and temperatures, whereas the one produced at 700°C displayed the highest corrosion rates. These findings suggest that the high entropy alloy produced at 1000°C is optimal for technological applications requiring high resistance to aggressive environments. The SEM images of corroded surfaces following exposure to aggressive environments substantiate these conclusions.